Management of free-ranging hunted wild reindeer (Rangifer tarandus) in Norway - Storass, Torstein, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2016)
In Europe, wild reindeer was an important source of human food during the last glaciation. Presently the last remnants of the wild European mountain living reindeer survive in southern Norwegian mountains where they move nomadically between summer and winter ranges. The reindeer ranges belong to different counties and municipalities and are owned by private persons and public institutions. The ranges are threatened by human development, and reindeer is a hunted species. The landowner has the hunting rights on own grounds. During a long political process, each reindeer mountain range has been defined, and regional development plans with zones of no development, buffer zones and zones with some development have been approved. A board of landowners and a national board with members from each municipality manage the reindeer according to the plan and National regulations. The national board has the right to oppose all development plans inside the reindeer ranges and will usually be heard by National authorities. The landowner board make harvest plans that must be approved by the national board. In this talk, I will describe the management system that is one example of how a vulnerable hunted species and its habitat crossing private and political borders may be managed.
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia.